Copyright and cloud computing - Власов, Іван Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article defines possible problems in the copyright regime, which appears in cloud computing process, basically on the analysis of the judicial practice of cloud computing cases, describes current and perspective vitality of the copyright in the cloud. The article doesn’t discuss the issue of copyright infringement by individual users; attention is paid to the issue of copyright protection by network intermediaries: ISPs and operators of sites and services that typically fall under the legal definition of the providers of "interactive computer services" or "providers of online services". Foreign scientists carried a series of theoretical studies on the problems of the copyright protection and cloud computing. For instance, the works of such scholars as Lessing L., Jonothan E., Pierre N. Leval, Scale M.-S. are devoted to the certain aspects of the copyright protection in the cloud. However, these problems are less explored in the national scientific opinion.